Decline in incidence of sudden cardiac death in the young: a 10-year nationwide study of 8756 deaths in Denmark. Issue 6 (26th February 2019) - Lynge, Thomas Hadberg; Nielsen, Jakob Lund; Blanche, Paul; Gislason, Gunnar; Torp-Pedersen, Christian; Winkel, Bo Gregers; Risgaard, Bjarke; Tfelt-Hansen, Jacob
Abstract: Aims: Sudden cardiac death in the young (SCDY) accounts for a significant proportion of deaths among the young. The aim of this nationwide study was to examine temporal changes in incidence and causes of SCDY in Denmark in 2000–2009. During this 10-year period, several public and private health initiatives were undertaken to decrease morbidity and mortality in Denmark. Methods and results: All deaths among persons aged 1–35 years in Denmark in 2000–2009 (23.7 million person-years) were included. Death certificates, autopsy reports, discharge summaries, and data from nationwide administrative registries were used to identify SCDY cases. Sudden cardiac death in the young incidence rates were age-adjusted and sex-adjusted using direct standardization. Temporal changes in standardized SCDY incidence rates were reported as average annual percent changes. In the 10-year study period, there were 8756 deaths, of which we identified 635 (7%) SCDY cases. For these SCDY cases, median age at death was 29 years and 68% were men. Standardized incidence of SCDY decreased from 3.1 per 100 000 person-years in 2000 [95% confidence interval (CI) 2.4–3.8] to 2.5 per 100 000 person-years in 2009 (95% CI 1.9–3.2). This corresponds to an average annual percent change of −3.0% (95% CI −5.8 to −0.1). The distribution of major causes of SCDY did not change significantly throughout the study period. Conclusion: Incidence of SCDY decreased significantly from 2000 through 2009 in Denmark with an average annual percent change of −3%. Further research is needed to elucidate underlying causes of this development.